Animal Genetic Resources and Biodiversity in the North-Eastern State of Assam, India: An Overview - Sarma, Olympica; Das, Bula; Phookan, Arundhati; Gogoi, Ankita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Assam is a rich repository of diverse livestock and poultry genetic resources, which form a vital component of global biodiversity. The region's indigenous livestock and poultry breeds are highly valued for their milk, meat, eggs, and adaptability. The unique genes and adaptive traits of these breeds hold immense potential for enhancing agricultural resilience, productivity, and sustainability in the face of future challenges. However, many native breeds are experiencing rapid genetic decline and dilution due to intensive production systems and the unregulated introduction of exotic germplasm. The conservation of animal biodiversity has become increasingly crucial in recent years as the rate of species extinction continues to accelerate. Numerous organizations have been instrumental in promoting development and conservation initiatives to protect livestock biodiversity. Assam is renowned for its rich diversity of indigenous livestock breeds. Among cattle, the region is home to the Lakhimi breed, while the unique Luit and Manah buffaloes add to its distinctiveness. In smaller hoofed animals, the Assam Hill goat is a notable native breed. The state also takes pride in its indigenous pig breeds, such as the Doom pig. Furthermore, Assam boasts hardy native poultry breeds like the Daothigir and Miri chickens, as well as the Pati duck, all well-adapted to local conditions. Additionally, the Manipuri horse, known for its cultural and historical significance, highlights the rich genetic diversity of Northeast, India. These valuable genetic resources highlight Assam’s significant role in conserving biodiversity and promoting sustainable livestock farming.